Experimental cardiovascular and lung researchMobilization of stem cells into the peripheral blood in children with congenital heart disease - Borówka, Magdalena; Stycuła, Wojciech; Kamycka, Elżbieta; Madeja, Zbigniew; Zuba-Surma, Ewa; Skalski, Janusz; Kołcz, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
The results of stem cell (SC) research in recent years have revealed real possibilities related to their use in the treatment of heart failure. The mobilization of different types of stem and progenitor cells is stimulated by stress factors. The presence of congenital heart defects and corrective surgery is associated with strong stressors that may stimulate the mobilization of SC. This work presents the preliminary results of research on stem cell mobilization of endothelial progenitor cells (EPCs), hematopoietic stem cells (HSCs), mesenchymal stem cells (MSCs), and very small embryonic-like (VSEL) stem cells in children undergoing surgical correction of congenital heart defects. Peripheral blood samples were collected from 21 children. The quality and quantity of stem cells were analyzed by classical and imaging (image stream) flow cytometry, while gene expression was evaluated through quantitative real-time RT-PCR. We determined the expression of genes characteristic of SC. Relevant statistical methods were used to assess the influence that some pathophysiological and demographic factors have on stem cell mobilization. In children with congenital heart defects, the mobilization of different types of SC is observed. The degree of mobilization depends on the pathophysiology of the defect and the patient’s age. Strong stress factors related to surgical correction of the defect significantly correlate with the degree of stem cell mobilization.